The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3847/1538-3881/ac8a44
|View full text |Cite
|
Sign up to set email alerts
|

SOFIA FEEDBACK Survey: PDR Diagnostics of Stellar Feedback in Different Regions of RCW 49

Abstract: We quantified the effects of stellar feedback in RCW 49 by determining the physical conditions in different regions using the [C ii] 158 μm and [O i] 63 μm observations from SOFIA, the 12CO (3–2) observations from APEX, and the H2 line observations from Spitzer telescopes. Large maps of RCW 49 were observed with the SOFIA and APEX telescopes, while the Spitzer observations were only available toward three small areas. From our qualitative analysis, we found that the H2 0–0 S(2) emission line probes denser ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…The "northern and southern clouds" reported in Figure 7 of Tiwari et al (2021) are identified as the red-colored cluster. The "pillar," which is reported as an independent structure in Tiwari et al (2022), is identified as a part of the southern cloud here (Figure 5). In previous studies (Tiwari et al 2021(Tiwari et al , 2022, the pillar is reported to be most intense in the velocity range of 5-15 km s −1 , which overlaps with the southern cloud (most intense within the velocity range of 2-8 km s −1 ).…”
Section: Gmm Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The "northern and southern clouds" reported in Figure 7 of Tiwari et al (2021) are identified as the red-colored cluster. The "pillar," which is reported as an independent structure in Tiwari et al (2022), is identified as a part of the southern cloud here (Figure 5). In previous studies (Tiwari et al 2021(Tiwari et al , 2022, the pillar is reported to be most intense in the velocity range of 5-15 km s −1 , which overlaps with the southern cloud (most intense within the velocity range of 2-8 km s −1 ).…”
Section: Gmm Resultsmentioning
confidence: 77%
“…The "pillar," which is reported as an independent structure in Tiwari et al (2022), is identified as a part of the southern cloud here (Figure 5). In previous studies (Tiwari et al 2021(Tiwari et al , 2022, the pillar is reported to be most intense in the velocity range of 5-15 km s −1 , which overlaps with the southern cloud (most intense within the velocity range of 2-8 km s −1 ). Morphologically, this pillar can be recognized as a separate structure, but kinematically, it is part of the southern cloud.…”
Section: Gmm Resultsmentioning
confidence: 77%
See 3 more Smart Citations